Centrapalus pauciflorus: Review of its Medicinal uses, Phytochemistry and Pharmacological Properties - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Centrapalus pauciflorus is a herbaceous plant that is used as a traditional medicine and a source of epoxidised oil. This study is aimed at providing a critical review of the pharmacological properties, phytochemistry and medicinal uses of C. pauciflorus. Documented information on the pharmacological properties, phytochemistry and medicinal uses of C. pauciflorus was collected from several online sources, which included Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as scientific publications, these, books, dissertations, book chapters and journal articles. This study showed that the leaves and epoxidised oil of C. pauciflorus are used as traditional medicines for external injury, wounds, diabetes, chest pains, eye infections, stomach problems and skin infections. Phytochemical compounds identified from the species include coumarins, essential oils, fatty acids, flavonol glycosides, phenolic acids, sterols, sesquiterpene lactones, triterpenoids, alkaloids, cardiac glycosides, carotenoids, flavonoids, polyuronoids, saponins, steroids, tannins and terpenoids. Pharmacological research revealed that C. pauciflorus extracts and compounds isolated from the species have analgesic, anti-dermatitis, antimicrobial, antiulcerogenic, hypoglycemic, insecticide, larvicidal and sedative activities. Centrapalus pauciflorus should be subjected to detailed phytochemical, pharmacological and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities.